Kendala Program Jaminan Kecelakaan Kerja pada Badan Penyelenggara Jaminan Sosial Ketenagakerjaan di Kota Padang - Diana Afrianita; Fitri Eriyanti (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
The research stems from the problem of worker complaints who are members of the Work Accident Security Program. These complaints include the relatively long time for disbursement of guarantees, the cost of recovery is still borne by workers and companies and workers who do not understand the procedures for the Work Accident Security Program at the Manpower Social Security Administration in Padang City. This type of research is qualitative research. This research was conducted at the Office of the Manpower Social Security Administration in the city of Padang. Technique of research informants was purposive. Data collection in this study was carried out by observation, interviews and documentation study. The results of this study indicate that the obstacles to Work Accident Security at the Employment Social Security Administration include long disbursement times, recovery costs are still borne by workers, companies are reluctant to pay medical expenses because they have to wait for confirmation from the Employment Social Security Administration, companies are late in sending. files in the case of work accident reports to the Manpower Social Security Administering Body.